The effects of wide vs. self-selected squat stance width on performance indices in elite rugby league players; an 8-week pre-season randomized controlled intervention - Sinclair, J.; Edmundson, C. J.; Taylor, P. J.; Grecic, D.; Jones, B.; Butters, B.; Bentley, I. (Movement & Sport Sciences - Science & Motricité, 2024)
This study examined the efficacy of wide compared to self-selected stance width squats in terms of mediating performance improvements during an 8-week period of pre-season training in elite rugby league players. Participants (N = 26) were randomly separated into either wide (N = 13) (i.e. self-selected squat stance width increased by 20%) or self-selected (N = 13) squat stance width training groups, and they completed an 8-week pre-season training block. Measures of 505-agility test time (primary outcome), 3 repetition maximum (3RM) squat strength in participants self-selected stance position and counter movement jump height were measured at baseline and 8-weeks. There were no significant differences between training groups in terms of the improvements made during the intervention period for 505-agility test (wide: pre = 2.47 ± 0.08 & post = 2.34 ± 0.11`s and self-selected: pre = 2.46 ± 0.05 & post = 2.35 ± 0.08`s), counter movement jump (wide: pre = 42.68 ± 9.57 & post = 44.65 ± 9.04 cm, and self-selected: pre = 49.33 ± 6.70 & post = 50.33 ± 4.67 cm) or 3RM squat strength (wide: pre = 159.00 ± 15.24 & post = 178.00 ± 19.32 kg and self-selected: pre = 168.33 ± 11.73 & post = 185.56 ± 16.48kg). As such the findings from the current randomized controlled trial suggest that there is not sufficient evidence to suggest that wide stance width squats represent a more efficacious method of resistance training prescription in elite rugby league.